Pelatihan Pengelolaan Keuangan bagi Usaha Mikro Kecil Menengah (UMKM) di Kecamatan Medan Helvetia - Free Antonius Simanjuntak (CV. Armas Suan Sejahtera, 2024)
The distribution of the number of MSMEs in Medan City is very easy to find. On average, MSMEs developing in Medan City are in the culinary, clothing and basic food sectors. The increasingly mushrooming growth of MSMEs actually adds value to the economy for families, regions and city governments. To support the development of MSMEs in Medan City, actually requires assistance from various parties from the government and academics. Academics in general can help MSMEs, especially with financial management issues. The aim of this community service activity is to provide knowledge and skills for MSMEs to be able to make financial reports for every transaction that occurs. This activity is divided into 3 implementation methods, namely the lecture method, tutorial method and question and answer method. The result of this service is that the knowledge and ability of MSME players in making financial reports has increased, which is demonstrated by enthusiasm and the results of working on questions to make financial reports in the form of general journal entries, trial balances, and profit and loss reports